2018
DOI: 10.1186/s12961-018-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for embedding a research culture in allied health practice: a rapid review

Abstract: BackgroundAlthough allied health clinicians play a key role in the provision of healthcare, embedding a culture of research within public and private health systems remains a challenge. In this rapid review we critically evaluate frameworks for embedding research into routine allied health practice, as the basis for high quality, safe, efficient and consumer-focused care.MethodsA rapid review (PROSPERO: CRD42017075699) was conducted to evaluate frameworks designed to create and embed research in the health sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 59 publications
1
115
0
2
Order By: Relevance
“…Three themes (‘supporting clinicians in research’, ‘working together’ and ‘valuing research for excellence) and 17 subthemes have been identified. Each subtheme is linked to a number of strategies which may be implemented at individual, team, organisational and policy levels as part of the ‘whole of system’ approach which has been recommended in the literature [ 12 , 33 , 36 , 45 ]. Although attempts were made to categorise strategies according to these structural levels, it was subsequently recognised that many strategies are applicable at more than one level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three themes (‘supporting clinicians in research’, ‘working together’ and ‘valuing research for excellence) and 17 subthemes have been identified. Each subtheme is linked to a number of strategies which may be implemented at individual, team, organisational and policy levels as part of the ‘whole of system’ approach which has been recommended in the literature [ 12 , 33 , 36 , 45 ]. Although attempts were made to categorise strategies according to these structural levels, it was subsequently recognised that many strategies are applicable at more than one level.…”
Section: Discussionmentioning
confidence: 99%
“…A research culture has been described as “an environment within an organisation that enables and supports research to generate new knowledge and opportunities to translate evidence into practice” [ 18 ] and has been reported to be essential for building research capacity [ 19 , 33 ]. Previous studies have found that senior management and leadership support for research appears to have a significant impact on an organisation’s research culture [ 7 , 20 , 35 , 36 , 46 ] and individual health professionals’ engagement in research [ 29 , 31 ]. The findings of this review further emphasise that in order to build and sustain research engagement, leaders and managers should recognise the benefits of having research-active practitioners in the workforce and consider research to be part of their core business alongside clinical practice [ 8 , 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personalised tapestries are created out of three interconnecting components (see Figure 2): (Slade et al, 2018). Conversely, known challenges include limited awareness of how to progress as a researcher, lack of time, funding, support, research infrastructure, knowledge and skills (Van Oostveen et al, 2017;White et al, 2013).…”
Section: Creating a Personalised Tapestrymentioning
confidence: 99%
“…Within the context of allied health, the aim of this process is to "strengthen existing practitioner expertise with complementary research" [19, p. 56] in order to enable high quality practice and advancement of the profession. Much effort has been made in recent decades to build research capacity and embed research cultures within the allied health professions [20][21][22][23][24]. Despite this, several barriers have been identified to establishing an effective research culture within this sector [8,25].…”
Section: Introductionmentioning
confidence: 99%